External validation of biomarkers for immune-related adverse events after immune checkpoint inhibition - Glehr, Gunther; Riquelme, Paloma; Yang Zhou, Jordi; Cordero, Laura; Schilling, Hannah-Lou; Kapinsky, Michael; Schlitt, Hans J.; Geissler, Edward K.; Burkhardt, Ralph; Schmidt, Barbara; Haferkamp, Sebastian; Hutchinson, James A.; et al. (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors have revolutionized treatment of advanced melanoma, but commonly cause serious immune-mediated complications. The clinical ambition of reserving more aggressive therapies for patients least likely to experience immune-related adverse events (irAE) has driven an extensive search for predictive biomarkers. Here, we externally validate the performance of 59 previously reported markers of irAE risk in a new cohort of 110 patients receiving Nivolumab (anti-PD1) and Ipilimumab (anti-CTLA-4) therapy. Alone or combined, the discriminatory value of these routine clinical parameters and flow cytometry biomarkers was poor. Unsupervised clustering of flow cytometry data returned four T cell subsets with higher discriminatory capacity for colitis than previously reported populations, but they cannot be considered as reliable classifiers. Although mechanisms predisposing some patients to particular irAEs have been described, we are presently unable to capture adequate information from pre-therapy flow cytometry and clinical data to reliably predict risk of irAE in most cases.